Precision National Driver License: Digital Application of Indonesian National Police as a Model of Public Service Transformation (Center for Public Policy and Digital Government Universitas Muhammadiyah Yogyakarta, 2024)
This article examines the adoption of the digital Precision National Driver's License (SINAR) application by the Traffic Corps of the Indonesian National Police as a paradigm for the modernization of public services. SINAR comprises e-Tilang, Traffic Management System (TMS), and SIM data input applications, which are designed to enhance traffic management and law enforcement. These applications streamline the ticketing process, enhance precision, and simplify the overall procedure. Furthermore, the National Police provides an internet-based portal for the submission of applications for international driver's licenses, which streamlines the application procedure. The implementation of these digital applications has greatly enhanced the operating efficiency and effectiveness of the National Police Traffic Corps while ensuring road safety and public satisfaction.